Prospect of Soybean Extensification in Indonesia - MULYANY, ANNY; SUKARMAN, .; HIDAYAT, ACHMAD (Indonesian Center for Agriculture Land Resource Development, 2009)
Indonesia which covers 188.2 million ha of land area has great opportunities for soybean expansion. Until now, domestic need for soybean is still complied from import. Soybean is one of the strategic commodities for food and industrial needs, which in 2008 became a national issue because of the scarcity in the market. Therefore, the Department of Agriculture launched a selfsufficiency policy on soybeans targetted in the year 2014 through breakthrough efforts. To support the target, suitable land for soybean has been identified in 17 provinces. The results showed that land suitable for soybeans is around 16.7 million ha, scatteredin various location, namely 4.9 million ha in wetland area, 1.7 million ha in dry land area, 1.7 million ha in plantation area, 2.9 million ha in mix garden area, and 5.5 million ha in grass land area. If 30% of the assumed land suitable for soybeans in ricefield and upland can be utilized, these can produce 2.4 million tons of soybeans with the assumption that the average productivity levels is 1.2 tonnes/ha and once a year planting to maintain the balance of others commodity production. By utilizing 2 million ha of ricefield and upland, soybean self-sufficiency can be achieved in 2015. The development and extensification of soybean planting area should consider land suitability level. Area selection which historically has became soybean production center in 1990 is also has to take into account as well as farmerâs habit in soybean farming system. To accelerate the soybean self sufficiency, the improvement of human resources must be supported in form of assisting, motivation, extention, training, and plot dmeonstration, in order to gain optimal land productivity and technological application. In addition, the government supports are needed for the provision ofproduction facilities, capital, building the marketing chain, as well as conditions to create reasonable prices so that there isincentive for communities to develop soybeans.